An Etiology of Sputum Culture Contamination and their Drugs Susceptibility Patterns among TB-suspected Patients at Epicentre Mbarara Research Centre, Uganda - Andrew Ajang Othow; Dan Nyehangane; Lucas Ampaire (Microbiology Research Journal International, 2024)
Aims: Contamination in TB cultures is problematic as it allows the growth of non-target bacterial or fungal species in sputum samples, potentially concealing M. tuberculosis. This study aimed to determine the prevalence, characterization, and drug susceptibility patterns of contaminants in sputum cultures from TB-suspected patients Methods: A laboratory-based cross-sectional study was conducted from October 2023 to June 2024 at the Epicentre Mbarara Research Centre, involving 81 sputum samples from TB-suspected patients. Conventional decontamination procedures were used, and both solid Lowenstein Jensen (LJ) and liquid Mycobacterium Growth Indicator Tube (MGIT) culture methods were applied. Standard culture techniques and physicochemical analyses were employed. Bacteria were incubated at 37°C in O2 and Co2 incubators, with growth observed within 24 to 48 hours and up to three days for yeast contaminants. Sabouraud Dextrose Agar cultures were monitored for two weeks for filamentous fungi. Antibiograms for bacterial isolates were determined using the Kirby Bauer, while broth microdilution was used for fungal isolates. Results: Of 81 samples, 14(17.28%) were contaminated. The most common bacterial contaminants were Staphylococcus aureus, Bacillus subtilis, Streptococcus viridans, Staphylococcus epidermidis, and Escherichia coli. Fungal contaminants included Aspergillus flavus, Penicillium species, Candida albicans, Cryptococcus neoformans, and non-albican Candida species. High resistance to erythromycin (73%) and tetracycline (50%) was noted among bacterial isolates, with sensitivity to vancomycin (67%), gentamycin (60%), and chloramphenicol (58%). Yeast isolates showed (87.5%) susceptibility to itraconazole and (75%) to amphotericin B but (50%) resistance to 5-flucytosine. Mold isolates exhibited (100%) susceptibility to itraconazole, amphotericin B, and 5-flucytosine but complete resistance to caspofungin. Conclusion: The level of contamination in TB cultures was noted, and Staphylococcus aureus and Candida albicans were observed as the most common contaminants. Bacterial isolates resisted erythromycin and tetracycline, while fungal isolates were generally susceptible to itraconazole and amphotericin B. We recommend Strengthening decontamination and monitoring common resistant contaminants.
Keywords: Bacterial; fungal contaminants; TB-suspects